A Study on the Influence of Enclosure Temperature Control on the Printing of ABS Filament in a Three-Dimension Printer - Jaber, Adil Sh.; Saleh, Ammar Mahdi; Ibraheem, Marwa Qasim (Engineering, Technology & Applied Science Research, 2025)
Fused Deposition Modeling (FDM) is a newest technique in additive manufacturing, capable of producing complex 3D parts efficiently and cost-effectively without using complicated or expensive dies. One of the most popular materials adopted in 3D printers is the ABS filament, which, despite its high mechanical properties, is susceptible to warping defects which can result in print failures. The objective of this study is to eliminate or minimize the warping defects by installing a temperature control system within the enclosure to prevent rapid cooling during the 3D printing process. The adopted design system uses a thermostat controller, a wire heater, and an enclosure to regulate temperature as required. A series of experimental tests were carried out using a range of sample shapes and sizes at three distinct controlled temperatures (40 °C, 50 °C, and 60 °C). The maximum measured error of 1.463 mm was observed at 40 °C. This variation was attributed to insufficient temperature control and a substantial sample volume of 2,827.44 mm3. Conversely, the minimum error of 0.223 mm was identified at higher temperatures of 60 °C, with a reduced sample volume of 530.14 mm3. The study determined that warping, in addition to layer shifting at vertical levels, is a significant contributor to the warping error. The present study recommends the use of an externally controlled temperature in order to enhance the quality and precision of 3D-printed ABS components.